<span>{(3, 7),(3, 6),(5, 4),(4, 7)}not
{(1, 5),(3, 5),(4, 6),(6, 4)}is
{(2, 3),(4, 2),(4, 6),(5, 8)}not
{(0, 4),(3, 2),(4, 2),(6, 5)}is</span>
Answer: (x - 2)² + (y - 14)² = 1
Step-by-step explanation:
<u>Concept:</u>
Here, we need to know the idea of the circle formula.
Circle formula: (x - h)² + (y - k)² = r²
Center = (h, k)
Radius = r
If you are still confused, please refer to the attachment below for a graphical explanation.
<u>Solve:</u>
Center = (2, 14)
Radius = 1
<em>Given formula</em>
(x - h)² + (y - k)² = r²
<em>Substitute the value into the formula</em>
(x - 2)² + (y - 14)² = (1)²
<em>Simplify</em>
(x - 2)² + (y - 14)² = 1
Hope this helps!! :)
Please let me know if you have any questions
Answer:
25 Or A
Step-by-step explanation:
X = 68
Since the angle opposite of it is a right angle, we know that 22 + x has to equal 90 also.
So just take 90 - 22 = 68 degrees
3.75 each, 6 friends, $20. 6 multiplied by 3.75 is 18.75. you can buy 5 sandwiches